The Relationship Between Family Support and Women's Readiness to Face Menopause - Layli Nur Aulia; Dewi Dolifah; Amanda Puspanditaning Sejati (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Menopause is a natural stage in a woman's life characterized by the permanent cessation of menstruation due to decreased ovarian function. This phase often causes various changes, both physically, psychologically, and emotionally, which can lead to discomfort for women. This study aims to examine the relationship between family support and women's readiness to face menopause. Method: This research is a quantitative study with a correlational analytic design. The research population consisted of women aged 45–55 years, with a sample size of 82 respondents selected using cluster sampling technique. The research instruments included a family support questionnaire by Nursalam, which had been declared valid (r table 0.336) and reliable (Cronbach’s Alpha 0.9453), as well as a questionnaire on women's readiness for menopause adapted from Agustina, which had been declared valid (r table 0.361) and reliable (Cronbach’s Alpha 0.886). The data were presented in the form of frequency distribution through univariate analysis and analyzed bivariately using the Spearman Rank test. Result: The study results indicate a significant relationship between family support and women's readiness to face menopause, with a correlation coefficient of 0.406 and a p-value <0.001, showing a moderate strength and a positive direction of the relationship. Conclusion: These findings indicate that the higher the family support provided, especially instrumental and emotional support, the better a woman's readiness to face menopause.